A sustainable mixotrophic microalgae cultivation from dairy wastes for carbon credit, bioremediation and lucrative biofuels. (October 2020) - Patel, Anil Kumar; Joun, Jaemin; Sim, Sang Jun
Graphical abstract: Novel Biochemical method enables to utilize highly organic whey strategically with reduced water usage for microalgae cultivation & pollutants remediation. Highlights: Highly organic whey normally requires higher dilutions (5–50 t) for algal-remediation. Biochemical method includes chemical treatments and algal treatment together. Low water usage greatly reduces the environmental burden and improve sustainability. This method able to treat inorganic and organic pollutants of whey upto 91–99.7%. Microalgae cultivation from pretreated whey improves carbon footprint of Industry. Abstract: Globally, high CO2 -emitting dairy industry obligated to treat waste and improve its carbon-footprints. Mixotrophic cultivation strategy (MCS) of microalgae enables to treat dairy wastes and mitigate CO2 for sustainable dairy economy. This study developed a biochemical process for organic whey with minimum dilution to avoid environmental burden. To make whey suitable for algae cultivation, it was pre-treated to remove polymers, unwanted solid fractions, opacity, and organic and inorganic overloads via acid hydrolysis, chemical flocculation and struvite formations with lowest dilution possible. 40% pretreated whey was most productive for biomass and lipid fractions respectively 4.54 and 1.80 gl −1 with daily productivities 0.50 and 0.20 gl -1 d -1, however 25% to reach adequate treatment. Overall, biochemical treatment was effective to remove respectively 99.7 and 91–100% of organic and inorganic pollutants, however algal treatment alone exhibited maximum 92.6 and 48.5–98.4% removals from both treatment ratios which is promising finding of this work.